A Myocutaneous Latissimus Dorsi Propeller Flap Based on a Single Dorsal Intercostal Perforator - Geierlehner, Alexander; Ludolph, Ingo; Arkudas, Andreas; Horch, Raymund E. (Plastic and Reconstructive Surgery Global Open, 2021)
This study presents a novel surgical technique for the reconstruction of highly challenging large lower back defects. In this case, a 72-year-old man initially diagnosed with renal cell carcinoma received nephrectomy followed by the dissection of an iliac crest metastasis and repeated high-dose irradiation therapy. Several years later, an osteocutaneous fistula at the right caudal posterior trunk made the reconstruction of the lower back defect necessary. High-dose irradiation of the lower back and poor vascular conditions at the pelvic region disqualified the patient for previously published local or free flap options. The initial strategy of an arteriovenous loop anastomosed to the femoral vessels and a free latissimus dorsi flap transfer had to be withdrawn due to repeated intraoperative loop thrombosis. For that reason, the entire latissimus dorsi muscle was used as a myocutaneous propeller flap receiving its blood supply solely through a single dorsal intercostal artery perforator. The flap survived completely and no fistulous formation occurred postoperatively. The time to complete wound healing was 4 months. This new technique is considered a valuable addition for the reconstruction of challenging posterior caudal trunk defects.
CRIS-Team WoS Importer:2021-12-03